Sodium citrate supplementation: An updated revision and practical recommendations on exercise performance, hydration status, and potential risks - Cerullo, G.; Parimbelli, M.; Perna, S.; Pecoraro, M.; Liguori, G.; Negro, M.; D`Antona, G. (Translational Sports Medicine, 2020)
Based on the assumption that a significant buffering capacity is able to attenuate the negative pH changes associated with high-intensity physical exercise, numerous studies have been focused on the effects of the exogenous administration of sodium citrate (SC) on human performance. However, the exact mechanisms of action of citrates have never been accurately described and results obtained so far often failed to demonstrate a significant advantage, mainly to an unfavorable relationship between achievable benefits and risk of side effects. In recent years, new evidence has emerged on the fields of use of SC supplementation in sports thus providing the theoretical basis for its use after dehydrating exercise to promote a fast fluid recovery. The aim of this review is to highlights recent experimental observations that could provide new interest in this buffering agent.